Plant–soil interactions regulate the identity of soil carbon in invaded ecosystems: implication for legacy effects. (12th December 2015) - Suseela, Vidya; Alpert, Peter; Nakatsu, Cindy H.; Armstrong, Arthur; Tharayil, Nishanth
Summary: Introduced, invasive plants can alter local soil chemistry and microbial communities, but the underlying mechanisms and extent of these changes are largely unknown. Based on characteristics associated with invasiveness in plants, it was hypothesized that introduced species that produce large amounts of litter with distinctive secondary compounds can a) alter the chemistry of both extractable and bulk carbon in the soil, b) shift microbial communities towards microbes better able to metabolize the compounds in the litter and c) cause soil carbon chemistry and microbial communities to shift to relatively uniform, novel states at multiple sites. Composition of phenolics in senescent tissues (leaves and roots) of Polygonum cuspidatum was compared to the composition of extractable phenolics and non‐extractable bulk organic carbon in soils under and adjacent to large, long‐established stands of P. cuspidatum at four sites in the eastern U.S. Rates of degradation of phenolics, activities of enzymes associated with the breakdown of phenolics and shifts in microbial community composition were also measured at the sites. Soils under P. cuspidatum stands contained twice as much phenolics as adjacent soils, but the composition of phenolics differed greatly between soils under stands and senescent tissues of P. cuspidatum . Flavonoids and proanthocyanidins constituted >90% of the identified phenolics in P. cuspidatum tissues, whereas monophenolic compounds accounted for >90% of the phenolics in soils under stands. Soils under and adjacent to stands also exhibited distinctive compositions of relatively persistent bulk organic carbon; composition differed less between soils under stands at different sites than between soils under and adjacent to stands at the same site. Soils under P. cuspidatum had 2·8 times greater abundance of fungi than soils adjacent to stands, and fungal markers showed clear separation of soils under and adjacent to P. cuspidatum . However, the potential activity of enzymes that degrade polyphenols was lower in soils under stands. Exogenously applied, chemically complex polyphenols persisted in both P. cuspidatum ‐invaded and adjacent non‐invaded soils, whereas less complex compounds rapidly disappeared from both soils. Synthesis . Results suggest that interactions between plant inputs, abiotic reactions and biotic transformations may create and maintain new states in invaded soils that are chemically and biologically less diverse. In the case of polyphenol‐rich, fast‐growing invasive species, these interactions may alter the composition of bulk soil organic matter that has relatively slower turnover rates, resulting in legacy effects. Restoration could thus require, not just removal of the species, but also post‐removal interventions such as soil amendments. Abstract : Lay Summary